2016
DOI: 10.22159/ijpps.2017v9i1.15487
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Potential Anti-Inflammatory Effect of Vitamin D3 Adjuvant Therapy for Chronic Asthma in Iraqi Patients

Abstract: Objective: This study was designed to evaluate the potential anti-inflammatory effect of vitamin D3 supplementation in Iraqi patients with chronic asthma.Methods: Forty-four candidate patients were diagnosed with asthma during their visit to hospital allocated as 20 patients assigned to receive conventional therapy for asthma and 24 patients assigned to receive conventional therapy for asthma plus 2000 I. U vitamin D3 tablet for three months period. Also, 30 apparently healthy subjects were included in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 40 publications
0
25
1
9
Order By: Relevance
“…A recent study observed many promising preventive strategies emerged from the available results since vitamin D relatively improve pulmonary function in asthmatic patients concomitantly with reduction of inflammatory burden in those patients, suggesting that vitamin D plays effective role to be a good candidate as an adjuvant therapy, but further evaluation is needed to explore the potential effect of vitamin D supplementation in acute or chronic asthma [61].…”
Section: Asthma and Chronic Kidney Diseasesmentioning
confidence: 99%
“…A recent study observed many promising preventive strategies emerged from the available results since vitamin D relatively improve pulmonary function in asthmatic patients concomitantly with reduction of inflammatory burden in those patients, suggesting that vitamin D plays effective role to be a good candidate as an adjuvant therapy, but further evaluation is needed to explore the potential effect of vitamin D supplementation in acute or chronic asthma [61].…”
Section: Asthma and Chronic Kidney Diseasesmentioning
confidence: 99%
“…Recent study found that vitamin D reduce inflammatory burden in asthmatic patient [31], while other studies have demonstrated alterations in different endogenous antioxidants in patients with asthma which may involve either an increase or a decrease pattern depending on the changes occurring due to a defense response [32]. In this study, the effect of vitamin D 3 supplementation on EC-SOD, SOD3 showed a significant increase in SOD3 antioxidant enzyme after 3 months treatment with vitamin D 3 supplementation to conventional therapy in Group 2 patients (p<0.05), meanwhile significant decrease of this enzyme activity after 3 months treatment with conventional therapy alone in Group 1 patients (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory effect of Vitamin D3 supplementation has been proved in patients with asthma [81].…”
Section: Treatment Approachesmentioning
confidence: 99%